The manifestations of social underdevelopment in Syria have had an impact on the development process - Abu Hamdan, Majid; saleh , Hala (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study deals with the most important manifestations of social underdevelopment in Syria and its impact on hindering the process of the comprehensive development of society. It is based on the need to eliminate the various aspects of social underdevelopment as a way to achieve social development in Syria and in various fields. The study deals with two main aspects: The decline in the level of education or illiteracy, the decline in the level of health, malnutrition, unemployment .... The second deals with the requirements for achieving development and thus eliminate the manifestations of social underdevelopment in Syria, through the development of development plans to get rid of these A phenomenon that we have mentioned, such as poverty In conclusion, several proposals were presented in order to contribute to achieving the objective of the study to eliminate the social underdevelopment prevalent in Syria as a way to achieve social development in various fields and to improve the Syrian society and transfer it to the ranks of the developed countries.